Preparation and characterization of smart hydrogels (magnetic field responsive) - Ghafil, Nagham Ali; Abdul-Majeed, Basma A.; Alsarayreh, Alanood A. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Iron nanoparticles were prepared by using the co-precipitation process, and then used to fabricate magnetic field-responsive hydrogel films. The magnetic nanoparticles’ structural, physical-chemical, morphological, and magnetic characteristics and the effect of hydrogel films’ coating concentration were studied. The properties of the hydrogel film responsive to the magnetic field were investigated using Fourier analysis spectroscopy infrared (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and a vibration sample magnetometer (VSM). The results indicated that all samples showed good inter-integration of the constituent materials and their functional groups. The hydrogel film samples which were polycrystalline, had broad diffraction peaks and showed constant particle size with nearly spherical particles with rounded edges. The SEM image of the magnetic nanoparticles with and without coating was established for the accumulation of numerous nanoparticles with a 17 nm mean diameter. In addition, the magnetic properties of the magnetic field-sensitive hydrogel films were evident and sufficient for drug delivery to the desired location.